Optimizing the Role of the Public Prosecutor in Handling Money Laundering Crimes (Central Jakarta District Court Decision Number 28/Pid.Sus-TPK/2020/PN Jkt.Pst): Optimalisasi Peran Jaksa Penuntut Umum dalam Penanganan Tindak Pidana Pencucian Uang (Putusan PN Jakarta Pusat Nomor 28/Pid.Sus-TPK/2020/PN Jkt.Pst) - Frizkana Meilia; Mikho Ardinata (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Handling money laundering crimes requires a comprehensive approach from law enforcement officials, including the central role of the Public Prosecutor (JPU) in the prosecution stage. This study discusses the optimal strategy used by the Public Prosecutor in handling money laundering cases, based on an analysis of the Central Jakarta District Court Decision Number 28/Pid.Sus-TPK/2020/PN Jkt.Pst. The method used is a normative juridical approach with qualitative data analysis techniques on decision documents and relevant laws and regulations. The prosecution of money laundering cases faces various challenges, such as complex financial transaction patterns and the use of fictitious identities. In this case, the prosecutor succeeded in proving the connection between the original criminal act and the act of money laundering using a reverse evidentiary approach. The cooperation between the prosecutor and the Financial Transaction Reporting and Analysis Center (PPATK) is a supporting factor in the preparation of detailed and argumentative indictments. Analysis of the verdict shows that careful preparation of indictments and the legal use of electronic evidence can strengthen the position of the prosecutor at the trial. In addition, collaboration between institutions also contributes to the effectiveness of prosecutions. This study provides an overview of the ideal practices for the prosecution of money laundering crimes in the criminal justice system in Indonesia and opens up opportunities for the development of litigation approaches that are adaptive to modern forms of financial crime.